Chemical residues and biochemical responses in wild and cultured European sea bass (Dicentrarchus labrax L.) - Fernandes, D (2020)
Cultured and wild sea bass (Dicentrarchus labrax) from the Arade Estuary were sampled in summer and winter and the degree of exposure to metals and polycyclic aromatic hydrocarbons (PAHs) assessed, together with some biochemical responses against those and other pollutants. The highest levels of copper (up to 997 microg g-1 dry weight) and cadmium (up to 4.22 microg g-1 dry weight) were detected in the liver and kidney of cultured specimens, whereas the highest exposure to PAHs was observed in wild fish. Significant alterations in some biochemical markers were detected and associated to pollutant exposure. Thus, metallothionein concentrations were higher in the tissues of cultured fish and positively correlated with metal residues. The activity 7-ethoxyresorufin O-deethylase ranged from 28 pmol/min/mg protein in cultured fish to 83 pmol/min/mg protein in wild fish collected near a marina area. Cultured fish and wild fish from the marina area had depressed acetylcholinesterase in muscle tissue and a parasitic infection in the gonads. The obtained results support the usefulness of the combined use of chemical and biochemical markers to assess the impact of anthropogenic pollutants in both wild and cultured fish.